1980
DOI: 10.1136/thx.35.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Fibreoptic bronchoscopy and diagnosis of pulmonary lesions in lymphoma and leukaemia.

Abstract: Fifty-six fibreoptic bronchoscopies were performed on 42 patients with Hodgkin's disease, lymphoma, or leukaemia and pulmonary complications which did not respond to conventional antibiotics. All these patients had received chemotherapy, radiotherapy, or both for the treatment of their underlying conditions. Twenty-two bronchoscopic procedures were complicated by thrombocytopenia and neutropenia, requiring platelet transfusion before bronchoscopy, and many patients were hypoxaemic. Visual examination of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…It is also not established whether there is any particular histological pattern associated with endobronchial HD [4]. In a review of 30 cases, no clear histological pattern was found [1,2,4,7,10,14]. Both our cases were of the nodular sclerosing type.…”
Section: Discussionmentioning
confidence: 64%
“…It is also not established whether there is any particular histological pattern associated with endobronchial HD [4]. In a review of 30 cases, no clear histological pattern was found [1,2,4,7,10,14]. Both our cases were of the nodular sclerosing type.…”
Section: Discussionmentioning
confidence: 64%
“…Fibre optic bronchoscopy disclosed a higher incidence (8/25, 32%) of endobronchial disease at presentation in patients with malignant lymphoma than has previously been appreciated (Gribetz et al, 1980;Phillips et al, 1980). The pattern of lymphomatous involvement varied with the histological type.…”
Section: Discussionmentioning
confidence: 76%
“…Several small series have examined the utility and complications of FB in immunocompromised patients with diffuse lung infiltrates [10, 11, 12, 13, 14, 15, 16, 17]. Most patients in these series were thrombocytopenic and received prophylactic platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%